"Inbox me, please": Analysing comments on anonymous Facebook posts about depression and suicide. Issue 5 (3rd September 2019) - Tao, Lane; Jacobs, Liezille
Abstract : This study explored Facebook posts for receptive disclosure and discussion of depression and suicidality among contributors. We utilised an existing data set of Facebook commentary from 445 comments made on 156 anonymous Facebook posts. A Chi-square analysis revealed that Facebook commenters provided positive support to those sharing their experiences of depression and suicide ideation. Only a small percentage of the responses (< 3%) were negative reactions. Our findings suggest that anonymous-to-visible social media communications may provide some form of social support, which could support e-psychology interventions.